Development of health tourism in Ukraine - Yavorska, Victoria; Nikolaeva, Maya; Grigoriev, Oleksandr (Journal of Education, Health and Sport, 2022)
The article examines the problems and prospects of the development of medical tourism. An analysis of the development and assessment of the current state of the health care complex in Ukraine was given. The article emphasizes that resort recreation should become a priority area for the future development of tourism in the state, as it can already provide significant foreign exchange earnings, contribute to the strengthening of the national monetary system and create additional jobs in this area. Centers of health tourism are sanatoriums and resorts of various medical profiles. The peculiarity of the tourist product in health tourism is its seasonal nature, the predominance of intra-regional trips and the specific age composition of consumers.